Damping-off defense: a comparative analysis of Trichoderma spp. (Hypocreales: Hypocreaceae) isolates against Sclerotium rolfsii (Polyporales: Atheliaceae) in groundnut - Chairunnisa, Eka; Masnilah, Rachmi; Nugroho Hadi, Zul Fauzi (Agrovigor, 2025)
Arachis hypogaea L. (Fabales: Fabaceae), a vital palawija commodity in Indonesia, has seen declining production in Jawa Timur in recent years. Among agricultural challenges, biotic factors like pest and disease infestations significantly impact yield. Damping-off, caused by the fungal pathogen Sclerotium rolfsii, is a major disease impacting groundnut cultivation. Biocontrol agents offer a promising alternative to synthetic fungicides for managing plant pathogens. This study evaluated the effectiveness of various Trichoderma spp. isolates in controlling S. rolfsii damping-off disease in Bison groundnut variety based on four key parameters: incubation period, disease incidence and severity, and control efficacy. The results demonstrated that all tested Trichoderma spp. isolates had the ability to suppress damping-off disease. Notably, isolate TB01 exhibited the best performance significantly prolonging the pathogen's incubation period, reducing disease incidence and severity in both pre- and post-emergence phases, and demonstrating the highest control efficacy 47.95% “sufficiently capable”. This study highlights the potential of Trichoderma spp. as a sustainable and eco-friendly biocontrol agent for managing S. rolfsii damping-off in groundnut cultivation. The successful application of isolate TB01 offers a promising approach for farmers seeking effective disease control strategies with minimal environmental impact.